Changes in fatty acid biosynthesis in marine microalgae as a response to medium nutrient availability - Fernandes, Tomásia (2021)
To maximize and enhance the fatty acid (FA) profiles of microalgae, it is crucial to understand the metabolic path ways that lead to high levels of the desired product. Nannochloropsis gaditana, Rhodomonas marina, and Isochrysis sp. were cultivated in media with various nutrient concentrations, and the biomass was analyzed for protein and fatty acid contents. The long chain polyunsaturated fatty acid (LC-PUFA) and protein contents were maximized in media with high nutrient concentrations. Under these conditions, the reduction in the (SFA + MUFA)/PUFA ratio (by as much as 83%) indicated that R. marina and N. gaditana shifted preference towards PUFA synthesis. The ∑ω3/∑ω6 ratio indicated that R. marina preferentially synthesized ω3 FA towards high nutrient concentrations (depicted by an eightfold increase) in contrast to Isochrysis sp. (which yielded a 35% reduction). In addition, the limitations of LC-PUFA biosynthesis at the level of its precursors (e.g. C18:2ω6, C18:3ω3, C18:4ω3) and further conversion to LC-PUFA as nutrients were increased, suggesting that external variations induced changes in the sets of enzymes that maintain the desaturation and elongation pathways of FA. The present study provides novel insights into the regulation of LC-PUFA biosynthesis and facilitates the modeling of microalgal FA patterns depending on the field of application.